2016
DOI: 10.1159/000452590
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Renin-Angiotensin System Antagonists in Maintenance Dialysis Patients

Abstract: Background/Aims: Whether angiotensin converting enzyme inhibitors (ACE) and angiotensin receptor blockers (ARB) are differentially associated with reductions in cardiovascular events and mortality in patients receiving maintenance dialysis is uncertain. We compared outcomes between ACE and ARB users among hypertensive, maintenance dialysis patients. Methods: National retrospective cohort study of hypertensive, Medicare-Medicaid eligible patients initiating chronic dialysis between 1/1/2000 to 12/31/2005. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…We excluded patients younger than 20 years old at the first prescription date, those who had more than 12 dialysis treatments within 180 days before the first prescription date, or who had received a catastrophic illness certificate for CKD with long-term dialysis before the first prescription date [16, 17]. We also excluded the renal transplant recipients (ICD-9-CM: 55.6, V42.0; procedure code: 76020B) at any time before the first prescription date.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded patients younger than 20 years old at the first prescription date, those who had more than 12 dialysis treatments within 180 days before the first prescription date, or who had received a catastrophic illness certificate for CKD with long-term dialysis before the first prescription date [16, 17]. We also excluded the renal transplant recipients (ICD-9-CM: 55.6, V42.0; procedure code: 76020B) at any time before the first prescription date.…”
Section: Methodsmentioning
confidence: 99%
“…Shireman et al. included 4997 patients undergoing dialysis (3555 ACEI and 1442 ARB users) and compared all-cause mortality and cardiovascular events [ 15 ]. In their study, ACEI use was associated with greater all-cause mortality and a trend toward an increased risk of cardiovascular events than ARB use.…”
Section: Discussionmentioning
confidence: 99%
“…Combination of ACEI and ARB increases the mortality of hemodialysis patients [33][34][35]. However, some studies have found that ARB drugs cannot reduce the risk of cardiovascular events and total mortality in long-term dialysis patients compared with other antihypertensive drugs [36][37].…”
Section: Discussionmentioning
confidence: 99%